(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2015)
For years, the importance of time as a legal asset deserving of protection was overlooked. The possibility of someone being compensated for the unjust and intolerable waste of their time was unimaginable. Today, using the rules of civil liability, especially with regard to the abuse of rights, and the consumer legislation, this liability is possible, since time is a value and as such deserves legal protection.